PONTA GROSSA: RUMO AOS PRESSUPOSTOS DA ROMANIZAÇÃO (Revista de História Regional, 2007)
The Diocesis of Ponta Grossa was created in 1930,when its first bishop, D. Antonio Mazzarotto was appointed. Awell-known preacher, with innate eloquence, he built animage of authority and fought for the truths of faith whichhe expressed in sermons, pastoral visits and also throughpastoral letters. In them he registered a program for theDiocese, a sacred placed crossed by multiple conflicts anddifferent views of the world, in an effort towards normatizingand unifying it.